Monitoring currents in cold-atom circuis - Safaei, S. (2020)
Complex circuits of cold atoms can be exploited to devise new protocols for the diagnostics of cold-atom systems. Specifically, we study the quench dynamics of a condensate confined in a ring-shaped potential coupled with a rectilinear guide of finite size. We find that the dynamics of the atoms inside the guide is distinctive of the states with different winding numbers in the ring condensate. We also observe that the depletion of the density, localized around the tunneling region of the ring condensate, can decay in a pair of excitations experiencing a Sagnac effect. In our approach, the current states of the condensate in the ring can be read out by inspection of the rectilinear guide only, leaving the ring condensate minimally affected by the measurement. We believe that our results set the basis for definition of new quantum rotation sensors. At the same time, our scheme can be employed to explore fundamental questions involving the dynamics of bosonic condensates.